People Powered Social Innovation: The Need for Citizen Engagement - Simon, Julie (Institutional Knowledge at Singapore Management University, 2013)
Citizen engagement is widely regarded as critical to the development and implementation of social innovation. What is citizen engagement? What does it mean in the context of social innovation? Julie Simon and Anna Davies discuss the importance as well as the implications of engaging the ground.